2023
DOI: 10.1039/d3qo00011g
|View full text |Cite
|
Sign up to set email alerts
|

Chiral oxalamide phosphine (COAP)-Pd-catalyzed enantioselective cascade formal [4 + 1] annulation for enantioenriched 2,3-disubstituted indolines and further DFT study on regio- and stereocontrol

Abstract: A chiral oxalamide phosphine (COAP)-Pd-catalyzed asymmetric cascade formal [4+1] annulation was developed between racemic vinyl benzoxazinones and N-tosylhydrazone sodium salts. The corresponding trans-2,3-disubstituted indoline products with contiguous stereogenic centers was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In consideration of the effect of strongly and weakly coordinating atoms on stereoselective control, our group has reported a series of chiral oxalamide phosphine (COAP) ligands by fusing an aryl phosphine unit with an oxamide moiety based on privileged axially chiral 1,2-diamine scaffolds. Those types of ligands with phosphoryl and carbonyl donor were modularly and facilely synthesized by the assemblage of chiral 1,2-diamines, oxalyl chlorides, and 2-(diarylphosphanyl) benzoic acids in four steps under mild reaction conditions . When the COAP ligands were employed for some palladium-catalyzed asymmetric intra- or intermolecular allylic alkylation reactions, good performance on both stereo- and regioselectivity was present by fine-tuning the steric and electronic properties of oxamide moieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consideration of the effect of strongly and weakly coordinating atoms on stereoselective control, our group has reported a series of chiral oxalamide phosphine (COAP) ligands by fusing an aryl phosphine unit with an oxamide moiety based on privileged axially chiral 1,2-diamine scaffolds. Those types of ligands with phosphoryl and carbonyl donor were modularly and facilely synthesized by the assemblage of chiral 1,2-diamines, oxalyl chlorides, and 2-(diarylphosphanyl) benzoic acids in four steps under mild reaction conditions . When the COAP ligands were employed for some palladium-catalyzed asymmetric intra- or intermolecular allylic alkylation reactions, good performance on both stereo- and regioselectivity was present by fine-tuning the steric and electronic properties of oxamide moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental outcomes and density functional theory calculations demonstrated that the oxamide coordination to palladium to form a favorable chiral environment is crucial for the corresponding regio- and enantioselective control. Inspired by the unique catalytic behavior of COAP in pallidum-catalyzed asymmetric allylic alkylation reactions, we proposed that COAP-palladium could catalyze asymmetric allylic alkylation of azlactones with MBH carbonates, which might provide an alternative approach for the construction of unnatural chiral α-amino acid derivatives. In this transformation, the catalyst must simultaneously control both linear regioselectivity and a chiral quaternary carbon center.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the reaction of 1a with B might form iridium-carbene E . Subsequent migratory insertion followed by reductive elimination via intermediates E and F delivers the final product and regenerates the iridium catalyst. From the control experiments listed in Scheme , path A might be suitable for the cyclization reaction.…”
mentioning
confidence: 99%
“…Most of the known annulation reactions limited to [ n + 3]-annulation where 3-diazoindoline-2-imines act as a three atom unit (Scheme a). To the best of our knowledge, [4 + 1]-annulation of 3-diazoindoline-2-imines with appropriate coupling partners is yet to be disclosed.…”
mentioning
confidence: 99%